2011
DOI: 10.1210/en.2010-0709
|View full text |Cite
|
Sign up to set email alerts
|

Impaired Hypothalamic Regulation of Endocrine Function and Delayed Counterregulatory Response to Hypoglycemia in Magel2-Null Mice

Abstract: Hypothalamic dysfunction may underlie endocrine abnormalities in Prader-Willi syndrome (PWS), a genetic disorder that features GH deficiency, obesity, and infertility. One of the genes typically inactivated in PWS, MAGEL2, is highly expressed in the hypothalamus. Mice deficient for Magel2 are obese with increased fat mass and decreased lean mass and have blunted circadian rhythm. Here, we demonstrate that Magel2-null mice have abnormalities of hypothalamic endocrine axes that recapitulate phenotypes in PWS. Ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
50
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(56 citation statements)
references
References 88 publications
5
50
0
1
Order By: Relevance
“…Tramadol influenced this activity where there was a reduction in the levels of LH, FSH and testosterone with induction of PRL and E2 levels. Previous studies concerned with gonadal activity during drugs abuse have been supported the present results where Tennese & Wevrick [30] reported decreased levels of LH and testosterone with increased prolactin hormone after morphine and methadone administration. Also El-Gaafarawi et al [21] observed the reduction of serum levels of LH, FSH and testosterone and the induction of prolactin hormone (PRL) and E2 secretions after cannabis use.…”
Section: Discussionsupporting
confidence: 91%
“…Tramadol influenced this activity where there was a reduction in the levels of LH, FSH and testosterone with induction of PRL and E2 levels. Previous studies concerned with gonadal activity during drugs abuse have been supported the present results where Tennese & Wevrick [30] reported decreased levels of LH and testosterone with increased prolactin hormone after morphine and methadone administration. Also El-Gaafarawi et al [21] observed the reduction of serum levels of LH, FSH and testosterone and the induction of prolactin hormone (PRL) and E2 secretions after cannabis use.…”
Section: Discussionsupporting
confidence: 91%
“…These data imply that a similar signaling and/or secretory mechanism might be disturbed in both ␤-and ␣-cells in TgPWS mice. Recent studies have shown a delayed counterregulatory response to insulin-induced hypoglycemia in mice deficient for the PWS region Magel2 gene, although pancreatic hormones were not assessed (62). Loss of Magel2 in TgPWS deletion mice may contribute in part to the more severe neonatal hypoglycemia and complete lack of a counterregulatory response described here for TgPWS mice.…”
Section: Discussionmentioning
confidence: 70%
“…Indeed, mouse Necdin has been implicated both in GnRH gene expression and the development of GnRH neurons, providing a potential molecular basis for gonadotropin deficiency in PWS (45). Similarly, Magel2 has recently been implicated in sex-specific endocrine changes putatively of hypothalamic origin, including GH release in response to ghrelin, in Magel2-null mice (62). These observations, combined with the pancreatic data presented here for the TgPWS mouse model, are consistent with a hypothesis that similar mechanisms underlie abnormal pancreatic, pituitary, and hypothalamic hormone and peptide secretion in PWS.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, truncating mutations of MAGEL2 result in Schaaf-Yang syndrome (MIM 615547) with marked clinical overlap to PWS, highlighted by hypotonia, hypogonadism, intellectual disability, and autism spectrum disorder (Schaaf et al, 2013). The Magel2 knockout mice recapitulate several of these phenotypes (Bischof et al, 2007; Kozlov et al, 2007; Mercer et al, 2009; Mercer and Wevrick, 2009; Tennese and Wevrick, 2011). This suggests that the regulation of WASH-mediated endosomal actin assembly and protein recycling by the MAGE-L2-TRIM27 ubiquitin ligase plays an important role in neurodevelopment.…”
Section: Introductionmentioning
confidence: 91%